Impact of Pupil Dilation on Optical Coherence Tomography Angiography Retinal Microvasculature in Healthy Eyes. Issue 11 (November 2020) - Villatoro, George; Bowd, Christopher; Proudfoot, James A.; Manalastas, Patricia I.C.; Nguyen, Khoa D.; Hou, Huiyuan; Penteado, Rafaella C.; Li, Andrew J.; Moghimi, Sasan; Ghahari, Elham; Weinreb, Robert N.; Zangwill, Linda M.
Abstract : Précis: Small but significant decreases in optical coherence tomography angiography (OCTA)-measured circumpapillary capillary density (cpCD) were observed in healthy eyes dilated with 2.5% phenylephrine/0.5% tropicamide. Although likely clinically insignificant, ophthalmologists should consider these changes when interpreting OCTA results from dilated eyes. Purpose: The purpose of this study was to investigate the effect of pupil dilation using 2.5% phenylephrine and 0.5% tropicamide on quantitative assessment of retinal microvasculature using OCTA. Methods: OptoVue AngioVue high density (HD) and non-HD OCTA macula and optic nerve head (ONH) images were obtained at 15-minute intervals predilation and postdilation in 26 healthy participants (mean age: 40.0; 95% confidence interval=33.9, 46.1 y). Superficial macular vessel density (VD) was measured in the whole image VD and the parafoveal region VD. ONH capillary density was measured in the whole image capillary density and the cpCD region. Differences between predilation and postdilation densities were assessed using linear mixed effects models to account for within-patient correlation. Results: Instillation of dilating drops resulted in a small but statistically significant reduction in non-HD ONH whole image capillary density of 0.6%, from a mean of 45.2% (95% confidence interval=41.9%, 48.4%) to 44.6% (41.4%, 47.8%) ( P =0.046). A similar reduction in non-HD ONH cpCD of 0.8% also was observed, from a mean of 49.3% (45.3%, 53.3%) to 48.5% (44.5%, 52.4%) ( P =0.025). No postdilation decreases in macular VD or HD ONH capillary density were observed. Conclusions: Pupil dilation using topical 2.5% phenylephrine and 0.5% tropicamide results in a small but statistically significant reduction in non-HD ONH whole image and cpCD in healthy eyes. The observed reduction likely is not clinically significant because the observed reduction was within the previously reported range of measurement variability. Further studies should consider investigating these effects in nonhealthy eyes with glaucoma and media opacities, as well as older individuals.